'A match made in midwifery': Women's perceptions of student midwife partnerships. Issue 2 (March 2020) - Jefford, Elaine; Nolan, Samantha J.; Sansone, Holly; Provost, Stephen C.
Abstract: Problem: Little is known regarding experiences of childbearing women participating in a Continuity of Care Experience. Background: Continuity of Care immersion is considered a vital component of undergraduate education in Australia. A student midwife follows a woman's childbearing journey regardless of the woman's individual needs or chosen model of care. Question: What do women value in their student-woman continuity experience, and does this vary with model of care provision ? Methods: Qualitative analysis was conducted on open-text box responses from 946 mothers enrolled in one regional university Continuity of Care program between 2014-2018. Findings: This qualitative descriptive study identified three overarching themes: 'Known student midwife'; 'Knowledge'; and, 'Professionalism'. The 'Known Student Midwife' was strongly associated with provision of support and advocacy for the woman and her partner/family. Women's responses were overwhelmingly positive, however, when some partnerships terminated, a negative impact was reported. Themes were often interlinked, suggesting when women valued one key attribute the others were somewhat related. Although rare, from some responses it was unclear if students had over-stepped professional boundaries, prompting the need for ongoing education. Discussion: This study provides compelling evidence for the perceived value of the Continuity of Care Experience in Australian midwifery curricula, as well as possible areas of concern regarding the nature of professional behaviour. Conclusions: Continuity of Care immersion plays a significant role in Australian midwifery education programs and is predominantly well received by childbearing women. Development of reflexive practice skills in undergraduate curricula may further enhance this experience for women.